David Cameron and the Web in the Run-up to the 2010 Election: A Parallel and Intricate Progression - Géraldine Castel (Revue LISA)
In 2005, following Michael Howard’s resignation and three successive General Election defeats, David Cameron was elected to head the Conservative party with the concept of modernisation as central to his rhetoric. In the same period, on both sides of the Atlantic, various experiments were conducted which attempted to integrate emerging tools in the sphere of information and communication technologies into politics. This article (written in 2011) therefore proposes to explore the parallel evolution of those two relative newcomers to national politics in the run-up to the 2010 General Election so as to analyse the relationship between them but also what such a relationship reveals both about David Cameron’s Conservative project and about the adoption of ICTs, and the internet in particular, in British political life.